The influence of immune system-related genes on the development of atopic dermatitis - Cieśla, Dominika; Nowak, Tomasz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2025)
Atopic dermatitis (AD) is a disease with a complex genetic background, in which only the predisposition to atopy is inherited. Genetic, environmental, and psychosomatic factors contribute to the development of this allergic inflammatory disease. The patient’s age and population affiliation also play a significant role. Gene groups associated with AD are primarily: genes responsible for the epidermal barrier, interaction with the environment and related to the immune response. In turn, polymorphisms in these genes can affect the severity of atopic dermatitis through mechanisms such as excessive stimulation of the immune system or increased synthesis of immunoglobulin E (IgE). Among the genes related to the immune system that play an important role in the development of atopic dermatitis, we can distinguish: Chitinase-3-like protein 1 ( CHI3L1 ), FceRI (Fc epsilon RI, ligand-binding subunit of the high-affinity IgE receptor), toll-like receptors ( TLRs ), and cytokine encoding genes.